Cannabis and amphetamine use and its psychosocial correlates among school-going adolescents in Ghana - Kwaku Oppong Asante (BMC, 2019)
Abstract Background The aim of this study was to examine the prevalence of cannabis and amphetamine use and to determine its associated factors among school-going adolescents in Ghana. Method The 2012 Ghanaian Global School-based Student Health Survey on 3632 adolescents aged 11-19 years (mean = 15.1 years; SD = 1.4) was used. Participants for this study were sampled from selected junior (JHS) and senior high schools (SHS) in all the 10 administrative regions of Ghana. A two-stage cluster sampling design was used to select 25 senior high schools to represent all the 10 regions of Ghana. Information was collected with a self-administered structured questionnaire that contained information on demographics, alcohol, tobacco and other drug use, violence, and a range of other health-related behaviours. Results The result showed that past-month cannabis use was 5.3% and lifetime amphetamine use was 7.1% among students. In multivariate model, after controlling for other variables, school truancy and current cigarette smoking were associated with both past-month cannabis and lifetime amphetamine use. The number of close friends was associated with only past-month cannabis use. School environment factors (bullying victimisation and having been attacked) and parental substance use were associated with lifetime amphetamine use. Conclusion This study identified a number of risk factors, including parental substance use and various risk behaviours, for both past-month cannabis and lifetime amphetamine use. School-based health intervention programmes should be developed taking into consideration the risk factors associated with cannabis and amphetamine use among school-going adolescents.